332 Patterns of care and outcomes of vulvar cancer treatment in women with or without HIV infection in Botswana. (13th November 2020) - Sakamuri, S; MacDuffie, E; Luckett, R; Moloi, T; Ralefala, T; Bvochora-Nsingo, M; Zetola, N; Grover, S
Abstract : Objective: Vulvar cancer rates are increasing in low-and middle-income countries with high incidence of HPV and HIV co-infection. Patterns of care in low-resource settings are not yet well described. Methods: Women with vulvar cancer who presented to an oncology clinic in Botswana from January 2015 through October 2019 were prospectively enrolled in this observational cohort study. Factors associated with survival including age, HIV status, stage, and treatment were evaluated. Results: 128 women with vulvar cancer were enrolled with a median age of 42 years. 46.6% presented at late stage (stage III/IV). 89% (n=107) of patients were living with a well-controlled HIV infection with a median CD4 count of 461 cell/ul (IQR 300.5–684.5) and high level of viral suppression (95% with viral copies < 400). Surgery was performed in 25 (20.8%) patients. 29 (24%) patients received chemotherapy. 81 (67.5%) received radiation therapy. Adjusted analysis controlling for HIV, age, stage, surgery, chemotherapy demonstrated no differences in survival at 32 months by HIV status (HR, 0.426; 95% CI, 0.112–1.5976). Older age (HR, 1.06; (95% CI, 1.02–1.11) was associated with worse survival while receipt of surgery was associated with improved survival (HR 0.09, 95% CI 0.01–0.74). Conclusions: Women in Botswana with vulvar cancer have a high rate of HIV infection and present at a young age. While decreased survival was associated with older age, HIV status did not impact survival. One-fifth of patients received surgery, which was associated with improved survival. Future efforts to identify patients early with limited disease burden and increase surgical capacity may improve outcomes.